Li-S and Li-O2 Batteries with High Specific Energy : Research and Development - Zhang, Huamin; Li, Xianfeng; Zhang, Hongzhang (Springer Singapore : Imprint: Springer, 2017)
This brief reviews the fundamentals, recent developments, challenges and prospects of Li-S and Li-O2 batteries, including fundamental research and potential applications. It starts with a brief overview encompassing the current state of Li-S and Li-O2 battery technology. It then provides general information on Li-S and Li-O2 batteries, including the electrochemical processes and battery components. The following sections focus on the historical and recent development of Li-S and Li-O2 batteries respectively, offering detailed insights into the key material development, cell assembly, diagnostic test and mechanism of electrolyte decomposition. Lastly, it focuses on the main promising applications of Li-S and Li-O2 batteries together with their challenges and potential.
Keywords: Energy.; Energy storage.; Electrochemistry.; Nanotechnology.; Materials science.; elektronické knihy; electronic books